Astrocyte Senescence and Alzheimer’s Disease: A Review - Han, Xiaojuan; Zhang, Tianying; Liu, Huanhuan; Mi, Yajing; Gou, Xingchun (Frontiers in Aging Neuroscience, 2020)
Astrocytes represent the largest group of glial cells and participate in a variety of essential functions in the healthy central nervous system (CNS) physiology, and disruption of their physiological roles can therefore be a contributor to CNS dysfunction and pathology. Cellular senescence, one of the mechanisms of aging, has been proposed as a central component of the age dependency of neurodegenerative disorders. The loss of astrocyte function or the gain of neuroinflammatory function as a result of cellular senescence could respond to both the neurofibrillary tangles and plaques of Alzheimer’s disease (AD), to tau hyperphosphorylation and Aβ accumulation. Senescent astrocytes may also lead to a deleterious set of effects including glutamate excitotoxicity, impaired synaptic plasticity, neural stem cell loss and blood-brain barrier (BBB) dysfunction during Alzheimer’s disease. In this review article, we summarize our growing understandings of cellular senescence in astrocytes, and its putative role in pathologic progress of Alzheimer's disease, and we will also discuss the significance of targeting senescent astrocytes as a novel and feasible therapeutic approach for AD.